Assessing the Impact of International Financial Reporting Standards (IFRS) through Bibliometric Research - Loso Judijanto; Tri Widyastuti Ningsih; Indah Wati; Sri Adella Fitri (The Es Accounting And Finance, 2023)
The present study evaluates the influence of International Financial Reporting Standards (IFRS) on scholarly literature through the utilization of bibliometric analysis. This study examines the frequency of occurrence of terms in a dataset consisting of renowned publications, thereby uncovering significant themes and areas of focus in IFRS research. Prominent terminology such as "Financial Reporting Standard," "Reporting," and "Accounting" indicate an exhaustive examination of the practical implementation of reporting standards and accounting principles. Underappreciated terminologies such as "Mandatory Adoption" and "Earnings Management" underscore intricate domains of inquiry, addressing the complexities and ramifications linked to the implementation of IFRS. The analysis reveals overarching themes such as sustained exploration, strategic considerations, and practical application, which offer valuable insights for both researchers and practitioners. The research contributes to the delineation of research priorities, the provision of instructional materials, the orientation of policy deliberations, and the resolution of pragmatic obstacles within the ever-evolving domain of IFRS research.